Designing a Career Advancement Model for Employees in Iranian Governmental Organizations (Case Study: Ministry of Economic Affairs and Finance) - Rajabi, Ahmad; Mehrabi, Javad; Mortazavi, Mehdi (Assessment and Practice in Educational Sciences, 2025)
The present study was conducted with the aim of designing a career advancement model for employees in Iranian governmental organizations, with the Ministry of Economic Affairs and Finance as the case study. In terms of purpose, the research was applied; in terms of data type, it followed a sequential mixed-methods approach with an exploratory orientation; regarding the research paradigm, it adopted a pragmatic stance; and in terms of nature, the qualitative phase was based on meta-synthesis and Delphi methods, while the quantitative phase was descriptive-analytical of the survey/correlational type. The qualitative research population included theoretical experts (university professors) and practical experts (relevant officials from the Ministry of Economic Affairs and Finance). Based on the principle of theoretical saturation and purposive sampling, 20 interviewees were selected. In the quantitative phase, the statistical population comprised all employees of the Ministry of Economic Affairs and Finance, from which 254 employees were selected through simple random sampling and based on the minimum sample size calculation required for confirmatory factor analysis. Data collection methods included Delphi in the qualitative phase and researcher-made questionnaires in the quantitative phase to assess the model’s validity both from the experts’ and respondents’ perspectives. The validity and reliability of the instruments were examined and confirmed in both qualitative and quantitative phases. Data analysis in the qualitative phase was conducted using thematic analysis via Maxqda-V18 software, while in the quantitative phase, descriptive and inferential statistics (confirmatory factor analysis and one-sample t-test) were performed using SPSS-V27 and SmartPLS-V3. The results indicated that career advancement in the Ministry of Economic Affairs and Finance comprises three dimensions: need-based career advancement, value-based career advancement, and talent-based career advancement. Need-based advancement includes autonomy, economic empowerment, and social status. Value-based advancement encompasses internal and external excellence, skill development, and knowledge enhancement. Talent-based advancement consists of technical and functional competencies, managerial qualifications, and creativity and innovation. The validation results further demonstrated that the proposed model possesses sufficient credibility, making it applicable for use by the Ministry of Economic Affairs and Finance to support employee career advancement.